Appropriateness of colonoscopy requests according to EPAGE-II in the Spanish region of Catalonia. Issue 1 (December 2015) - Marzo-Castillejo, M.; Almeda, J.; Mascort, JJ; Cunillera, O.; Saladich, R.; Nieto, R.; Piñeiro, P.; Llagostera, M.; Cantero, FX.; Segarra, M.; Puente, D.
Abstract Background In a context of increasing demand and pressure on the public health expenditure, appropriateness of colonoscopy indications is a topic of discussion. The objective of this study is to evaluate the appropriateness of colonoscopy requests performed in a primary care (PC) setting in Catalonia. Methods Cross-sectional descriptive study. Out-patients >14 years of age, referred by their reference physicians from PC or hospital care settings to the endoscopy units in their reference hospitals, to undergo a colonoscopy. Evaluation of the appropriateness of 1440 colonoscopy requests issued from January to July 2011, according to the EPAGE-II guidelines (European Panel on the Appropriateness of Gastrointestinal Endoscopy). Results The most frequent indications of diagnostic suspicion requests were: rectal bleeding (37.46 %), abdominal pain (26.54 %), and anaemia study (16.78 %). The most frequent indications of disease follow-up were adenomas (58.1 %), and CRC (31.16 %). Colonoscopy was appropriate in 73.68 % of the cases, uncertain in 16.57 %, and inappropriate in 9.74 %. In multivariate analysis, performed colonoscopies reached an OR of 9.9 (CI 95 % 1.16–84.08) for qualifying as appropriate for colorectal cancer (CRC) diagnosis, 1.49 (CI 95 % 1.1–2.02) when requested by a general practitioner, and 1.09 (CI 95 % 1.07–1.1) when performed on women. Conclusions Appropriateness of colonoscopy requests in our setting shows a suitable situation in accordance with recognized standards. General practitioners contribute positively to this appropriateness level. It is necessary to provide physicians with simple and updated guidelines, which stress recommendations for avoiding colonoscopy requests in the most prevalent conditions in PC.